Konsep Fenomenologi Edmund Husserl dan Relevansinya dalam Konsep Pendidikan Islam - Nugraheni, Shofi; Marchela, Dwi Putri; Al Ghozali, Syifa Kamila; Ahya', Muhammad Khoirul; Nasikhin; Junaedi, Mahfud; Martina Roesner (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2023)
Edmund Husserl popularized the concept of phenomenology. According to what we know about philosophy, Husserl was a philosopher who had strong opinions about phenomena. When discussing psychology, Husserl's biography is written about Husserl's life story, his writings, and the resources available for higher education. From Husserl's Phenomenological Theory, the evaluation method used is Library Research, which is a term for the type of analysis carried out by collecting data from all available sources. Refers to the books designated as data sources. Phenomenology is a distinct discipline.In the years (1857-1938). Phenomology is a single branch of science that is often called radical, because it is based on assumptions that threaten the integrity of the human body's innate mental processes. Undersucgsuhugen Logik, Iden Zuenier Rainen's "phanomenologie und phanomenologischen" philosophy, and Cartesian Meditations are among the key works that Husserl left behind. Thought and Epoche-Related Writings, Husserl's views on naturalistic psychology, phenomena, and phenomenology as an academic discipline. One of the principles of education, according to Edmund Husserl, is interpersonal communication. Other principles include critical thinking and engaging in activities that cause a person to feel uncomfortable.